2007
DOI: 10.1016/j.jacc.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Stent Thrombosis, Myocardial Infarction, and Death After Drug-Eluting and Bare-Metal Stent Coronary Interventions

Abstract: The minor risk of ST and MI within 15 months after implantation of DES seems unlikely to outweigh the benefit of these stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
2
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(149 citation statements)
references
References 23 publications
5
136
2
6
Order By: Relevance
“…The clinical trials have proved that DES can not only prevent the in-stent restenosis caused by early postoperative vascular wall recoil and long-term negative remodeling, but also can significantly reduce the in-stent restenosis caused by smooth muscle cell proliferation and neointimal hyperplasia. Though some studies [7,8] have found that DES could increase the risk of late stent thrombosis, clinical trails have proved that DES could significantly improve the long-term prognosis of patients with CHD. [3,4,[8][9][10] Since domestic DES Firebird was marketed in 2003, several other types of domestic DES have been put into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical trials have proved that DES can not only prevent the in-stent restenosis caused by early postoperative vascular wall recoil and long-term negative remodeling, but also can significantly reduce the in-stent restenosis caused by smooth muscle cell proliferation and neointimal hyperplasia. Though some studies [7,8] have found that DES could increase the risk of late stent thrombosis, clinical trails have proved that DES could significantly improve the long-term prognosis of patients with CHD. [3,4,[8][9][10] Since domestic DES Firebird was marketed in 2003, several other types of domestic DES have been put into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…3) [14,15] and in 2006 the situation went out of control. Then the uncontested i ncreased risk of stent thrombosis at around 1 year of follow-up was inappropriately highlighted in an isolated manner by several reports [16,17]. They failed to point out clearly enough that they focused on the time around 1 year and they did not acknowledge the respective advantage in favour of DES accrued over the first year.…”
Section: Figurementioning
confidence: 99%
“…9,16,18,20,21,33 However, the reduction of subsequent revascularization in registries was less than in clinical trials. The absolute reduction in target vessel revascularization at 4 years in a network meta-analysis of 38 clinical trials was about 12 vs. 2 -4% in the Swedish SCAAR registry at 3 years.…”
Section: Efficacymentioning
confidence: 99%